Not Simply Returning to the Same Answer Over and Over Again: Reframing Relevance - Hodgkinson, Gerard P.; Starkey, Ken (British journal of management, 2011)
From its earliest days, the field of business and management studies has wrestled with fundamental questions concerning its nature and purpose: for whom and to what ends is scholarly research ultimately directed? However, amid unprecedented changes to the world of work, over the past two and a half decades these questions have become of central importance to academicians, practitioners and policy‐makers. The British Academy of Management (BAM), through the work of its Research Policy Committee and the British Journal of Management, has played a central role in these developments. This paper traces the lineage of BAM's contribution and offers a critical assessment of the current state of play with regard to the so‐called relevance problem, arguing that design science and critical realism have the potential to take the field forward by transcending the ‘either/or’ game into which the rigour versus relevance debate has a tendency to develop.